FORMATION OF DIGITAL PLATFORM CAPABILITIES FOR STUDENTS IN PROFESSIONAL EDUCATION - Muhayyo Shakirovna Salixova; Dilnavoz Bahodirova (Bright Mind Publishing, 2025)
This article examines the impact of digital educational platforms on the educational process and the quality of education in vocational education institutions. In addition, the article analyzes the pedagogical and didactic possibilities of digital technologies, their role in increasing students' knowledge, effective control of learning, and individualization of the educational process. It is also discussed that as a result of the use of digital platforms, the effectiveness of teaching methods has increased, which has a positive impact on the learning outcomes of students. According to the research results, it is shown that digital educational platforms are important in improving the quality of education.
Keywords: digital platforms, professional education, improving the quality of education, teaching methods, educational process, didactic opportunities, improving students' knowledge, learning control, individualization of the educational process, effectiveness, learning outcomes.